Variabilite Et Prevision Des Extremes Climatiques Dans Le Bassin De La Lobo (Centre-Ouest De La Cöte D’ivoire) : Apport Des Chaines De Markov Et Du Generateur De Temps Mulgets - N’GUESSAN Bi, Vami Hermann; ADJAKPA, Tchépko Théodore; ALLECHY, Fabrice Blanchard; YOUAN TA, Marc; ASSA, Yapi Fabrice; AFFIAN, Kouadio (My University, 2020)
In recent decades, Côte d'Ivoire has been faced with a high level of climate variability, which has led to numerous natural disasters. The objective of this study is to analyse and predict climate extremes based on daily rainfall data from 1984 to 2013. The MulGETS weather generator based on Markov chains of order 1 and the index calculation method were respectively used to predict the precipitation fields from 2021 to 2050 and calculate the PRCPTOT (total annual precipitation), R1mm (number of rainy days), R10mm (number of days of intense rainfall) and R20mm (number of days of very intense rainfall) indices. During the period 1984 to 2013, the northern half of the Lobo basin is characterized by PRCPTOT ranging from 503.7 mm to 2566.12 mm with R1mm not exceeding 265 days. R10mm can reach a maximum of 52 days with R20mm ranging from 1 day to 28 days. The extreme south of the basin gives rise to PRCPTOT not exceeding 2363.8 mm with R1mm ranging from 149 days to 301 days. R10mm extends over a period of 73 days with R20mm ranging from 1 day to 19 days. Over the period from 2021 to 2050, the northern half of the basin will be marked by PRCPTOT not exceeding 1916mm with R1mm up to 244 days. R10mm will vary from 16 days to 56 days with R20mm ranging from 5 days to 27 days. As for the extreme south of the basin, PRCPTOT will be between 1047.03 mm and 1720.03 mm with R1mm ranging from 194 days to 266 days. R10mm may extend over a maximum of 52 days with R20mm not exceeding
Keywords: Climatic extremes; Chain Markov; MulGETS; Lobo